Separation of different conformations of plant mitochondrial DNA molecules by field inversion gel electrophoresis - Scissum-Gunn, Karyn D.; Gandhi, Medha; Backert, Steffen; Nielsen, Brent Lynn (Plant Molecular Biology Reporter, 1998)
Mitochondrial (mt) DNA structure in higher plants is still unclear as to the circularity or linearity of the genome. We have developed a system to electrophoretically separate distinct populations of mtDNA, with some populations enriched for networked linear and circular DNA molecules. Using field inversion gel electrophoresis (FIGE) and electron microscopy (EM), we have identified four distinct populations of mtDNA from two Brassica species. Using FIGE, two slow migrating mtDNA populations ran faster than a 66 kbp Escherichia coli circular plasmid marker, while these same populations comigrated in the compression zone in contour-clamped homogeneous electrophoretic field (CHEF) gels. A fast-migrating mtDNA population was also resolved by FIGE as a diffuse band between 20 to 70 kbp when compared with linear lambda (lambda) markers. FIGE resolved the 66 kbp circular marker into several multimers, while CHEF resolved only open-circular monomers and linears. In agreement with FIGE results, EM analysis indicated the two slow migrating mtDNA populations contained circular (both supercoiled and relaxed circles) and free linear molecules of 10-60 kbp, and networked linear molecules of 45-140 kbp total size that may represent recombination intermediates. The fast migrating population consisted of 10-50 kbp linear molecules. Well-bound mtDNA showed only long linear molecules of 40-150 kbp with no detection of circles or complex/rosette molecules. This report shows that FIGE has clear advantages over CHEF for separating large DNA molecules with different conformations, and may be very useful for studies to characterize genome structure in complex systems such as plant mitochondria.
Keywords: field inversion gel electrophoresis; genome structure; plant mitochondrial DNA